Determinants of waterpipe smoking in Iranian adults: results from the IROPICAN study - Seyyedsalehi, Monireh Sadat; Shah, Aneri; Rashidian, Hamideh; Hadji, Maryam; Marzban, Maryam; Ansari-Moghaddam, Alireza; Nejatizadeh, Azim; Boffetta, Paolo; Zendehdel, Kazem (Frontiers in Psychiatry, 2023)
Introduction: Waterpipe smoking has become increasingly popular in Western countries, particularly among young individuals. This study aims to identify the factors influencing waterpipe smoking by focusing on consumption patterns. Methods: We utilized data from a multicenter case-control study (IROPICAN) conducted in Iran. Multivariate logistic regression estimated the adjusted odds ratio and 95% confidence intervals as a measure of association between waterpipe smoking and different factors. Results: Among 3477 subjects were included, 11.8% were waterpipe smokers. Most of <50 years old smokers were occasional (80%), while daily smokers were often >50 years (85%). Around 59 % of occasional users started it before 30 years old. Low education, low SES, alcohol consumption, cigarette smoking, secondhand smoke exposure, and opium use were associated with waterpipe smoking. Stratified analysis by frequency pattern showed an association between occasional smoking with age 0.97(0.96-0.98), university degree 0.36(0.17-0.76), urban dwellers 1. 40(1.06-1.86) and between high SES and daily smoking 0.34(0.17-0.69).Our results offer valuable information to policymakers for developing waterpipe smoking control measures. The occasional waterpipe smoking results may be generalized to the younger people in Western countries.